Bringing Parenting Interventions Back to the Future: How Randomized Microtrials May Benefit Parenting Intervention Efficacy. (March 2015) - Leijten, Patty; Dishion, Thomas J.; Thomaes, Sander; Raaijmakers, Maartje A. J.; Orobio de Castro, Bram; Matthys, Walter
Abstract : A novel approach is needed to promote the efficacy of parenting interventions designed to improve children's mental health. The proposed approach bridges developmental and intervention science to test which intervention elements contribute to parenting intervention program efficacy. The approach encourages the field to move "back to the future" using stringent, focused experimental techniques to test discrete parenting techniques (e.g., praise, time‐out) on their merit. We argue that these randomized microtrials are needed to (a) distinguish between the less and more efficacious elements of parenting interventions, (b) illuminate for whom and under what conditions elements are efficacious, and (c) explore the potential for empirically supported tailoring of interventions to meet families' specific needs.